An Amino Acids on Bali Cattle and Wagyu Beef Based on Different Function of Muscle (ASAM-ASAM AMINO SAPI BALI DAN DAGING SAPI WAGYU BERDASARKAN FUNGSI OTOT YANG BERBEDA) - Besung, I Nengah Kerta; Rasdianah, Rasdianah; Suardana, I Wayan; Suwiti, Ni Ketut (Jurnal Veteriner, 2019)
Beef is an essential source of protein and several functional compounds that are very important for human. The quality of beef depends on both genetic and environmental factors like feed, age, sex, and others. This research aimed to determine the composition of amino acids both Bali and Wagyu beef on the different activity of muscle, i.e. active and passive. As many as 5 g of each sample was used in this study. The active beef samples were presented by Biceps femoris, and passive beef samples were presented by Longissimus dorsi. High-Performance Liquid Chromatography (HPLC) method was used in order to an identification of amino acids according to the standard procedure. Results of the study showed that the essential amino acids content both bali cattle and wagyu were higher than non-essential, and amino acids content originated from active muscle was higher than passive muscle. Methionine, phenylalanine, and serine on bali beef cattle were lower than wagyu beef. Overall, the content of amino acids essential was lower than non-essential. In conclusion, there is no significant difference of amino acids content both bali cattle and wagyu beef, but the function of muscle (active or passive) were known contribute to the difference of amino acids content.